2002
DOI: 10.1016/s0168-1591(01)00191-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications of coping characteristics and social status for welfare and production of paired growing gilts

Abstract: This paper considers the question whether knowledge on individual coping characteristics of growing pigs may be used to improve welfare and production after mixing. Gilts with either reactive or proactive coping characteristics were identified according to behavioural resistance in a backtest, respectively, being low (LR) and high resistant (HR) in this test. At 7 weeks of age, several pairs of unfamiliar gilts were formed, and pairs and dominance relationships were studied over a 3-week period. The following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…The association between welfare-related carcass lesion frequency and average CCW is unsurprising; previous Visibility of welfare lesions in slaughter pigs research has found that skin and tail lesions are associated with reduced feed intake and growth due to the effects of infection and stress (Wallgren and Lindahl, 1996;Ruis et al, 2002;Marques et al, 2012). Lower carcass weights are a source of indirect financial loss to producers (Harley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The association between welfare-related carcass lesion frequency and average CCW is unsurprising; previous Visibility of welfare lesions in slaughter pigs research has found that skin and tail lesions are associated with reduced feed intake and growth due to the effects of infection and stress (Wallgren and Lindahl, 1996;Ruis et al, 2002;Marques et al, 2012). Lower carcass weights are a source of indirect financial loss to producers (Harley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to categorize individual pigs within a test group according to certain coping styles reflecting individual adaptive patterns of behavior and physiology to the surrounding environment (Bolhuis et al, 2003(Bolhuis et al, , 2005aD'Eath and Burn, 2002;Forkman et al, 1995;Hessing et al, 1993;Janczak et al, 2003;Ruis et al, 2000Ruis et al, , 2002van der Kooij et al, , 2003. In most of these studies, the possible characterization of pigs was according to their inclinations to respond either actively (proactive) or passively (reactive) to different situations, which is a well-known phenomenon in many animal species (for review, Koolhaas et al, 1999).…”
Section: Behavioral Testing Of Pigsmentioning
confidence: 99%
“…Studies in rodents basically distinguish between proactive and reactive coping (Koolhaas et al, 1986 [rats]; van Oortmerssen et al, 1985 [mice]) and studies in fish and birds often use the terms shyness and boldness (Wilson et al, 1994). In pigs, the concept of coping is also supported, although the extremes in the population do not represent distinct categories of pigs (Ruis et al, 2002; Zebunke et al, 2015). Studies focusing on coping styles in animals suggest that the proactive response is characterized by a typical active fight-flight response in aversive situations which is associated with territorial control, aggression and risk-taking (Cannon, 1929; Benus et al, 1990; Mount and Seabrook, 1993; Koolhaas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%